2017
DOI: 10.1093/sleep/zsx083
|View full text |Cite
|
Sign up to set email alerts
|

Sudden Unexpected Death During Sleep in Familial Dysautonomia: A Case–Control Study

Abstract: Initiation of noninvasive ventilation when required and discontinuation of fludrocortisone treatment may reduce the high incidence rate of SUDS in patients with FD. Our findings contribute to the understanding of the link between autonomic, cardiovascular, and respiratory risk factors in SUDS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 38 publications
(39 reference statements)
0
22
0
Order By: Relevance
“…Early identification of sleep abnormalities in patients with FD is key as treatment of SDB with non-invasive ventilation has been reported to reduce the risk of sudden unexpected death during sleep in this population. 10 …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Early identification of sleep abnormalities in patients with FD is key as treatment of SDB with non-invasive ventilation has been reported to reduce the risk of sudden unexpected death during sleep in this population. 10 …”
Section: Discussionmentioning
confidence: 99%
“…1,10 We recently reported that untreated sleep-disordered breathing (SDB) increases the risk of sudden unexpected death during sleep in patients with FD. 10 Therefore, identification and treatment of SDB is important to prevent premature death in this population. 1,6,10 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Patients have varying degrees of upper airway obstruction (83%), lower airway disease (85%), and restrictive lung disease (94%) (NYU FD Registry 2016). Approximately 85% of adults and 91% of pediatric patients [15] have some degree of sleep-disordered breathing which, when untreated, is a risk factor for sudden unexpected death during sleep (SUDS), a leading cause of death in FD [13]. …”
Section: Epidemiology Of Respiratory Disorders In Fdmentioning
confidence: 99%
“…Hallmarks of FD include impaired pain and temperature sensation, reduced basal tear production [4], absent deep tendon reflexes, optic neuropathy [5], gait ataxia [6], blood pressure instability owing to afferent baroreflex failure [7-9], neurogenic dysphagia [10], chemoreflex failure [11, 12], sleep-disordered breathing [13-15], and chronic lung disease [16], all which contribute to morbidity and mortality [3, 13]. Respiratory disease remains one of the leading causes of death in patients with FD [3].…”
Section: Introductionmentioning
confidence: 99%